10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background People with tuberculosis (TB) have a suicide risk up to 25 times higher than the general population. It may be due to stigma, isolation, prolonged treatment, and psychological distress from the disease. Hence, empowering healthcare workers (HCWs) who are involved in TB care with suicide prevention skills is essential. Novelty This study will be integrating suicide prevention into TB care and will be evaluating an asynchronous learning management solution (LMS)-based training model against traditional in-person gatekeeper training for HCWs of high-risk population. Objectives This study will examine the effectiveness of the gatekeeper suicide prevention training online e-module compared to in-person training for National Tuberculosis Elimination Program (NTEP) HCWs. Methods HCWs in the Karnataka State NTEP program will be randomly assigned to two training groups using parallel cluster-randomization at the district level. The online training group (intervention group) will receive training through customized and locally adapted e-modules hosted on an LMS. The In-person training group (control group) will undergo training through presentations, role-play simulations, and discussions. Training effectiveness will be assessed using the Kirkpatrick model, with statistical evaluation and comparison of pre- and post-test scores to measure knowledge acquisition, skill retention, and application (number of referrals) across both groups. Expected outcome The study anticipates that e-module training will be as effective as in-person training for developing competence and confidence in suicide prevention and early identification and referral of suicidality.